Plasmacytoid urothelial carcinoma of the bladder - Meihua Qin; Gangping Wang; Yanqing Sun; Qun He (Wolters Kluwer Medknow Publications, 2014)
Plasmacytoid urothelial carcinoma (PUC) of the urinary bladder is an uncommon and aggressive variant of urothelial carcinoma associated with late presentation and poor prognosis. Immunohistochemical examination showing expression of epithelial markers, CD138, and losing the membranous expression of E-cadherin confirms evidence of PUC. Here, we report a case of bladder PUC of a 74-year-old male who presented with hematuria. A transurethral biopsy revealed urothelial carcinoma with plasmacytoid appearance. The diagnostic dilemmas of this unusual variant of urothelial malignancy and its clinical impact are discussed. The pathological diagnosis was PUC (High-grade, pT4N2M0) with diffuse muscle, small tracts, and vascular invasion, in which almost of the areas studied on the tissue section showed Plasmacytoid differentiation.